2009
DOI: 10.1007/s12011-009-8445-3
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effect of Organic Gallium on Ovariectomized Osteopenic Rats by Decreased Serum Minerals and Increased Bone Mineral Content

Abstract: The purpose of this study was to verify the effect of organic gallium on ovariectomized osteopenic rats. Thirty Wistar female rats used were divided into three groups: (1) sham-operation rats (control), (2) ovariectomized (OVX) rats with osteopenia, and (3) OVX rats with osteopenia treated with organic gallium. Treatments were performed over an 8-week period. At sacrifice, the fifth lumbar vertebral body, one tibia, one femur, and the fourth lumbar vertebrae were removed, subjected to micro-CT for determinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 16 publications
(16 reference statements)
1
13
0
Order By: Relevance
“…Elemental gallium alters the mineral [27,28], matrix, and cellular properties of bone. According to animal experiments, yeast-incorporated gallium has been demonstrated the effect on ovariectomized osteopenic rats by decreased serum minerals and increased bone mineral content [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elemental gallium alters the mineral [27,28], matrix, and cellular properties of bone. According to animal experiments, yeast-incorporated gallium has been demonstrated the effect on ovariectomized osteopenic rats by decreased serum minerals and increased bone mineral content [10].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the anti-osteoporosis element such as gallium is effective in the treatment of osteoporosis in ovariectomized rats by decreased serum minerals and increased bone mineral content [10]. Yeast-incorporated gallium (YG) as an organic compound not only reduces elements-associated toxicity but also maintains its therapeutic effect [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Organic gallium compounds, such as gallium maltolate or yeast incorporated gallium, have better bioavailability and lower toxicity and are better candidates for an alternative antiosteoporotic treatment. [118,119].…”
Section: Galliummentioning
confidence: 99%
“…In this context, we were interested in finding new anti-resorptive compounds. Given the potential anti-resorptive effects of gallium (Ga) suggested by a few studies (Donnelly et al, 1991;Blair et al, 1992;Ma and Fu, 2009), we focused our efforts on the effect of Ga on osteoclasts.…”
Section: Gallium Modulates Osteoclastic Bone Resorption E Verron Et Almentioning
confidence: 99%
“…In a small trial of myeloma patients treated with chemotherapy, Ga was shown to attenuate the rate of bone loss in patients (Niesvizky, 2003). Moreover, treatment with organic Ga was shown to improve bone content and strength in osteopenic rats (Ma and Fu, 2009). All these data suggest that Ga may have a positive effect on these bone disorders, probably by decreasing the rate of bone resorption.…”
Section: Introductionmentioning
confidence: 99%